Wpływ decyzji inwestycyjnych i finansowych na elastyczność strategiczną przedsiębiorstwa - Jajuga, Teresa (Influence of Investment and Financing Decisions on the Strategic Flexibility of an Enterprise, 2007)
In the paper strategic flexibility is defined. Then it is shown how one can create flexibility by appropriate investment and financing decisions. In addition, main real options are presented -exercising these options enables real changes in the operation of the enterprise caused by changes in the environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 165-172